Molecular Phylogeny of the Leafy Liverwort Lejeunea - Heinrichs, Jochen; Dong, Shanshan; Schäfer-Verwimp, Alfons; Pócs, Tamás; Feldberg, Kathrin; Czumaj, Aleksandra; Schmidt, Alexander R; Reitner, Joachim; Renner, Matt A. M; Hentschel, Joern; Stech, Michael; Schneider, Harald (PloS one, 2013)
Lejeunea is a largely epiphytic, subcosmopolitan liverwort genus with a complex taxonomic history. Species circumscriptions and their relationships are subject to controversy; biogeographic history and diversification through time are largely unknown. We employed sequences of two chloroplast regions (trnL-trnF, rbcL) and the nuclear ribosomal ITS region of 332 accessions to explore the phylogeny of the Harpalejeunea-Lejeunea-Microlejeunea complex. Lejeunea forms a well-supported clade that splits into two main lineages corresponding to L. subg. Lejeunea and L. subg. Crossotolejeunea. Neotropical accessions dominate early diverging lineages of both main clades of Lejeunea. This pattern suggests an origin in the Neotropics followed by several colonizations from the Neotropics into the Paleotropics and vice versa. Most Afro-Madagascan clades are related to Asian clades. Several temperate Lejeunea radiations were detected. Eighty two of the 91 investigated Lejeunea species could be identified to species level. Of these 82 species, 54 were represented by multiple accessions (25 para- or polyphyletic, 29 monophyletic). Twenty nine of the 36 investigated species of L. subg. Lejeunea were monoicous and 7 dioicous. Within L. subg. Crossotolejeunea, 15 of the 46 investigated species were monoicous and 31 dioicous. Some dioicous as well as some monoicous species have disjunct ranges. We present the first global phylogeny of Lejeunea and the first example of a Neotropical origin of a Pantropical liverwort genus. Furthermore, we provide evidence for the Neotropics as a cradle of Lejeunea lineages and detect post-colonization radiations in Asia, Australasia, Afro-Madagascar and Europe. Dioicy/monoicy shifts are likely non-randomly distributed. The presented phylogeny points to the need of integrative taxonomical studies to clarify many Lejeunea binomials. Most importantly, it provides a framework for future studies on the diversification of this lineage in space and time, especially in the context of sexual systems in Lejeuneaceae.